POLA ASUH BALITA IBU-IBU KELOMPOK SASARAN PADA PROGRAM KEGIATAN BINA KELUARGA BALITA USIA 0–12 BULAN DUSUN GANDEKAN KARTASURA - Hastasari, Chatia; Anggitya, Paramastu Titis; Musslifah, Anniez Rachmawati (Informasi, 2015)
AbstractThe rapid advancement of information technology was not enough to bring change in the attitude of the mothers in applying good parenting on their children. There are still many women who apply parenting capital only a myth or hereditary habits. The impact of the low level of understanding about parenting maternal age, especially toddlers 0-12 months of this should be a serious concern of all parties concerned, as stem from the application of good parenting toddlers that we can prepare the next generation of quality. The purpose of this study was to determine the parenting toddlers of mother target groups Program BKB aged 0-12 months during which also evaluated from the perspective of communication. This study was designed using a "Research and Development". Results of this study when viewed from the perspective of communication, communication models on parenting toddlers applied by mothers of the target group in the success of the family development program of children aged 0-12 months are interactional model.AbstrakMajunya teknologi informasi tidak cukup membawa perubahan dalam sikap ibu dalam menerapkan pola asuh yang baik bagi anak-anak mereka. Masih banyak wanita mengasuh berdasarkan "mitos" atau kebiasaan turun-temurun. Dampak dari rendahnya tingkat pemahaman tentang pengasuhan, terutama balita 0-12 bulan ini harus menjadi perhatian serius dari semua pihak.Pasalnya, hal ini terkait dengan mempersiapkan generasi masa depan berkualitas. Tujuan dari penelitian ini adalah untuk menentukan pola pengasuhan balita kelompok sasaran Program BKB berusia 0-12 bulan yang dievaluasi dari perspektif komunikasi. Penelitian ini dirancang dengan menggunakan "Research and Development". Hasil penelitian ini adalah jika dilihat dari perspektif komunikasi, model komunikasi pada pengasuhan balita yang diterapkan oleh ibu dari kelompok sasaran keluarga anak usia 0-12 bulan adalah model interaksional.Keywords: Interactional models, BKB Program, Parenting Toddlers.